The pan-plastome of Prunus mume: insights into Prunus diversity, phylogeny, and domestication history - Wang, Jie; Kan, Junhu; Wang, Jie; Yan, Xinlin; Li, Yi; Soe, Thida; Tembrock, Luke R.; Xing, Guoming; Li, Sen; Wu, Zhiqiang; Jia, Minlong (Frontiers in Plant Science, 2024)
Prunus mume in the Rosaceae and commonly referred to as mei or Chinese plum is widely used as a traditional ornamental flowering plant and fruit tree in China. Although some population and genetic analyses have been conducted for this species, no extensive comparisons of genetic variation from plastomes have yet been investigated. Here, we de novo assembled the plastomes of 322 P. mume accessions and constructed a pan-plastome level resource of population structure and genetic diversity. The assembled plastomes exhibited a typical quadripartite structure and ranged from 157,871 bp to 158,213 bp in total size with a GC content ranging from 36.73 to 36.75%. A total of 112 unique genes were identified. Single nucleotide variants (SNVs) were the most common variants found among the plastomes, followed by nucleotide insertions/deletions (InDels), and block substitutions with the intergenic spacer (IGS) regions containing the greatest number of variants. From the pan-plastome data six well-supported genetic clusters were resolved using multiple different population structure analyses. The different cultivars were unevenly distributed among multiple clades. We also reconstructed a phylogeny for multiple species of Prunus to better understand genus level diversity and history from which a complex introgressive relationship between mei and other apricots/plums was resolved. This pattern indicates that the domestication of P. mume involved multiple genetic origins and possible matrilineal introgression from other species. These results provide an important maternal history for Prunus and lay groundwork for future studies on intergenomic sequence transfers, cytonuclear incompatibility, and conservation genetics.